Functional Interaction between Human Herpesvirus 6 Immediate-Early 2 Protein and Ubiquitin-Conjugating Enzyme 9 in the Absence of Sumoylation - Tomoiu, Andru (American Society for Microbiology, 2006)
The immediate-early 2 (IE2) protein of human herpesvirus 6 is a potent transactivator of cellular and viral promoters. To better understand the biology of IE2, we generated a LexA-IE2 fusion protein and screened, using the yeast two-hybrid system, a Jurkat T-cell cDNA library for proteins that could interact with IE2. The most frequently isolated IE2-interacting protein was the human ubiquitin-conjugating enzyme 9 (Ubc9), a protein involved in the small ubiquitin-like modifier (SUMO) conjugation pathway. Using deletion mutants of IE2, we mapped the IE2-Ubc9-interacting region to residues 989 to 1037 of IE2. The interaction was found to be of functional significance to IE2, as Ubc9 overexpression significantly repressed promoter activation by IE2. The C93S Ubc9 mutant exhibited a similar effect on IE2, indicating that the E2 SUMO-conjugating function of Ubc9 is not required for its repressive action on IE2. No consensus sumoylation sites or evidence of IE2 conjugation to SUMO could be demonstrated under in vivo or in vitro conditions. Moreover, expression levels and nuclear localization of IE2 were not altered by Ubc9 overexpression, suggesting that Ubc9's repressive function likely occurs at the transcriptional complex level. Overall, our results indicate that Ubc9 influences IE2's function and provide new information on the complex interactions that occur between herpesviruses and the sumoylation pathway.